OP1 Severity-dependent gene expression in canine myxomatous mitral valve disease. (5th April 2020) - Markby, Greg; Macrae, Vicky; Summers, Kim; Corcoran, Brendan
Abstract : Myxomatous mitral valve disease (MMVD) is the most common canine cardiovascular disease and shares many similarities with human mitral valvulopathies. While transcriptomic datasets are available for the end-stage disease in both species, there is no information on how gene expression changes as the disease progresses, such that it cannot be stated with certainty if the changes seen in end-stage disease are casual or consequential. In contrast to humans, the disease in dogs can be more readily examined as it progresses, and this allows an opportunity for insight into disease pathogenesis relevant to both species. The aim of this study was to identify changes in valve gene expression as canine MMVD advances over an entire life-time, from normal (grade 0) to severely affected (grade 4), and differences in gene expression comparing normal and disease areas of the same valve. Transcriptomic profiling identified 1002 differentially expressed genes (DEGs) across all four disease grades when compared with normal valves (>1.5 or <1.5 fold change, p-value <0.05, >3.8 log2 signal intensity) with the greatest number of DEGs in grade 3 (673) and grade 4 (507). DEGs were associated with a large number of gene families, including genes encoding for cytoskeletal filaments, peptidases, extra-cellular matrix (ECM) proteins, chemokines and integrins. Gene enrichment analysis identified significant grade-dependent changes in gene clustering, with clusters trending both up and down. Significant grade-dependent changes in disease hallmark gene expression intensity, including ACTA2, HTR2B, MMP12 and CDKN2A, was identified. Gene Ontology terms were dominated by terms for ECM and inflammation with TGFβ1, TNF, IFGN identified as the top up-stream regulators in both whole and dissected diseased valve samples. These data show that while disease progression in MMVD is associated with increasing numbers of DEGs, TGFβ appears to be the dominant signalling pathway controlling pathogenesis irrespective of disease severity.